Implementasi Aplikasi SAKTI dalam Pengelolaan Keuangan APBN di Direktorat Jenderal - Haryanto, Haryanto; Soemartono, Triyuni; Rachmatsyah, T. Herry (Publika: Jurnal Ilmiah Administrasi dan Kebijakan Publik, 2025)
This study aims to conduct an in-depth evaluation of the implementation of digitalization policies in state financial management through the application of the Institutional-Level Financial Application System (SAKTI) within the Directorate General of Regional Financial Development. This initiative is intended to enhance transparency, accountability, and efficiency in managing the State Budget (APBN). Using a descriptive qualitative approach, the study examines the implementation of SAKTI based on George C. Edwards III’s policy implementation theory, which emphasizes communication, resources, disposition, and bureaucratic structure. The findings indicate that SAKTI has had a positive impact, particularly in improving administrative efficiency, the accuracy of transaction recording, and the ease of financial monitoring and reporting. Nevertheless, several challenges persist, including communication barriers, limited resources, and bureaucratic resistance. Therefore, it is necessary to strengthen policy dissemination efforts, provide continuous training for human resources, and improve technological infrastructure to ensure the more effective and sustainable implementation of SAKTI in supporting a more transparent and accountable state financial governance.